Assessing the role of Co-curricular programs in improving vocational skills in the Tertiary level among the Volta region schools - Tibu, Judith; Agbai Bissi, Emefa; Ama Wornyo, Rejoice; Kludze Akorfa , Rosemary; Appiah, Margaret (Yayasan Sahabat Literasi Edukasi dan Publikasi Bandung, 2025)
This study assesses the effect of co-curricular programs towards promoting Visual Arts and Home Economics instruction in four tertiary institutions within the Volta Region of Ghana: Ho Technical University, Evangelical Presbyterian University College, Akatsi College of Education, and St. Francis College of Education. Utilizing a descriptive survey design, 171 participants (150 students, 15 lecturers, and 6 coordinators of programs) were surveyed using questionnaires and interviewed. Findings indicate widespread student participation in co-curricular training that is largely focused on the development of general skills and not vocational practice. Limited resources and poor industry linkage prevent the development of practical skills. Suggested solutions are the inclusion of more vocation-specific training, stronger industry partnership, and resource investment to develop students' vocational readiness and employability.